1990
DOI: 10.1007/bf01021019
|View full text |Cite
|
Sign up to set email alerts
|

Strong repellency of the root knot nematode,Meloidogyne incognita by specific inorganic ions

Abstract: Simple inorganic salts of the ions K(+), NH 4 (+) , Cs(+), NO 3 (-) , and Cl(-) are strongly repellent to infective second-stage larvae of the root knot nematode,Meloidogyne incognita. Some of these salts are known to be beneficial to plant growth. The results suggest a new means of plant protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 4 publications
3
25
0
Order By: Relevance
“…The influence of various types of soil on the distribution of nematodes has been reported by many Ž authors Castro et al, 1990;Norton, 1979Norton, , 1989. Prot and van Gundy, 1979 .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of various types of soil on the distribution of nematodes has been reported by many Ž authors Castro et al, 1990;Norton, 1979Norton, , 1989. Prot and van Gundy, 1979 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific ions, on the other hand, may attract or repel nematodes (1,2,33) and thereby affect the number of nematodes encountering conidia. Similarly, specific ions and osmotic potential may enhance or suppress Hirsutella rhossiliensis (5,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Vinasse application in the study area may have influenced the results described because it is a residue rich in organic matter, which provides energy (carbon) to edaphic microfauna, thus promoting biomass increasing and its activity (MENG et al, 2009). Vinasse also presents high levels of potassium and the presence of this ion in the soil can cause plant-parasitic nematode population reduction, as it interferes with the development of certain species of the genus Meloidogyne (CASTRO et al, 1990). This corroborates the study conducted by Pedrosa et al (2005), who observed a reduction of juvenile hatching and a population density of M. incognita and M. javanica after vinasse application.…”
Section: Resultsmentioning
confidence: 99%